Low intensity focused ultrasound induces reversal of tumor-induced T cell tolerance and prevents immune escape - Bandyopadhyay, Sanmay (J Immunol, 2016)
Immune responses against cancer cells are often hindered by immunosuppressive mechanisms that are developed in the tumor microenvironment. Induction of a hyporesponsive state in tumor antigen-specific T cells is one of the major events responsible for the inability of the adaptive immune system to mount an efficient anti-tumor responses and frequently contributes to lessen the efficacy of immunotherapeutic approaches. Treatment of localized tumors by focused ultrasound is a minimally invasive therapy that uses a range of input energy for in situ tumor ablation through the generation of thermal and cavitation effect. Using a murine B16 melanoma tumor model, we show that a variant of focused ultrasound that delivers a reduced level of energy at the focal point and generates mild mechanical and thermal stress in target cells, has the ability to increase immunogenic presentation of tumor antigens, which results in reversal of tumor-induced T cell tolerance. Furthermore, we show that the combination of non-ablative low energy focused ultrasound with an ablative hypofractionated radiation therapy results in synergistic control of primary tumors and leads to a dramatic reduction in spontaneous pulmonary metastases while prolonging recurrence free survival only in immunocompetent mice.